Lead like Jesus : lessons from the greatest leadership role model of all times - Blanchard, Kenneth H.; Hodges, Phil. (Nashville, TN : Thomas Nelson, 2005)
"Learn how to lead like Jesus, whether in the home, the church, the community, or the marketplace; moving not only from success to significance but taking a step beyond significance--surrender"--Provided by publisher.
Introduction : the lead like Jesus journey -- Who will you follow? How will you lead? -- The heart of a servant leader -- The head of a servant leader -- The hands of a servant leader -- The habits of a servant leader --Why lead like Jesus? -- Next steps to lead like Jesus.
Includes bibliographical references (p. 237-239)
Keywords: Jesus Christ -- Leadership; Bible. -- Criticism, interpretation, etc; Leadership -- Religious aspects -- Christianity; Leadership -- Biblical teaching